Colopexy through celiotomy as treatment of recurring rectal prolapse in cats - Sánchez R., Ivan Camilo (2021)
The case of two cats with recurrent rectal prolapse is presented; 3- and 5-month-old male and female, respectively. The clinical examination revealed two patients with body condition 2/5, pale mucous membranes, dehydration and a prolapse of approximately 6 cm of the rectum with the presence of housefly larval structures. The tutor reports that a month before the consultation, the cats were rescued and underwent digital reduction with suture in the anus as a corrective measure for a first rectal prolapse that recurred fifteen days after said intervention. As an urgent corrective measure, and after stabilizing the patients, a colopexy was performed through celiotomy, using polyglactin 910 for this purpose. There were no intraoperative and postoperative complications. During 12 months after colopexy, there was no recurrence of prolapse in any of the patients.